2005
DOI: 10.4319/lo.2005.50.6.1707
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rates of cadmium between a burrowing mayfly and its surroundings in nature

Abstract: We conducted a reciprocal transfer of nymphs of the burrowing mayfly Hexagenia limbata between two rivers harboring populations of this insect that differed in their cadmium (Cd) concentrations. We measured Cd uptake and loss rates simultaneously in the field at several levels of biological organization: in the gut and body of whole nymphs as well as in three subcellular fractions. The most marked changes in Cd concentrations occurred in the insect's gut, where Cd was largely associated with heat-stable protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…This variation in sizes could be expected, based on analysis by Corkum and Hanes (1992), who suggested that a range in mayfly nymph lengths is attributable to a wide range of hatching times and nutrient availability, and hence larval size may not be a good indicator of larval age. Furthermore, Bartsch et al (1999) and Michaud et al (2005) demonstrated that nymphs accumulate a substantial amount of Cd within only a few weeks residence time in sediments. Therefore, the metal contents in the nymphs analyzed in this study are correlated to the metal contents available in the sediments and do not reflect residency time.…”
Section: Hexageniamentioning
confidence: 96%
See 3 more Smart Citations
“…This variation in sizes could be expected, based on analysis by Corkum and Hanes (1992), who suggested that a range in mayfly nymph lengths is attributable to a wide range of hatching times and nutrient availability, and hence larval size may not be a good indicator of larval age. Furthermore, Bartsch et al (1999) and Michaud et al (2005) demonstrated that nymphs accumulate a substantial amount of Cd within only a few weeks residence time in sediments. Therefore, the metal contents in the nymphs analyzed in this study are correlated to the metal contents available in the sediments and do not reflect residency time.…”
Section: Hexageniamentioning
confidence: 96%
“…Hence, trophic transfer of Cd in mayflies may increase with increased sediment concentration because the Cd is in the sediment in the gut of the mayfly as well as in the gut tissue (Hare et al, 1989;Cain et al, 2004). Michaud et al (2005) concluded that Cd in the mayfly's gut was largely associated with heat-stable proteins such as the metal-binding protein metallothionein (in the cytosol), and these proteins, and thus associated metals, are readily available to consumers (i.e., fish) who assimilate metals from the cytosolic fraction of their food. Hence, the accumulation of Cd in the mayflies in the western basin of Lake Erie is of particular concern due to the high Cd levels found in the sediments, which exceeded the TEL at 27 of 28 sites and the PEL at 9 of 28 sites, and due to the potential for ready transfer to consumers.…”
Section: Hexageniamentioning
confidence: 99%
See 2 more Smart Citations
“…Hexagenia was chosen because it is a large-bodied mayfly that lives in soft sediments, is an indicator of ecosystem health in the Great Lakes (Edsall 2001), and has been used extensively in both toxicity and bioaccumulation assays (Henry et al 1986, Gobas et al 1989, Milani et al 2003, Michaud et al 2005, Smith et al 2008, Van Geest et al 2011, Harwood et al 2014. Also, Hexagenia has an intermediate sensitivity (Milani et al 2003) and slightly lower tolerance score (6) than S. femoratum (7) (Bode et al 2002), making it a conservative addition to the study.…”
Section: Laboratory Experimentsmentioning
confidence: 99%